Ultracompact Multiaxis Force Sensor Based on Sensitivity Amplification Mechanism for High-Sensitivity and Capacity Measurement - Lee, Seran; Jung, Dawoon; Hwang, Jinhak; Kim, Uikyum (IEEE/ASME Transactions on Mechatronics, 2025)
In recent years, increasing research focus has been devoted to force sensing for delicate tasks in robotic applications. This has led to increased requirements for force sensors with enhanced sensitivity, broader measurement ranges, and more compact designs. In this study, a compact three-axis force sensor based on an enhanced sensitivity amplification mechanism is introduced for high sensitivity and capacity measurements. The mechanism has a C-shaped comb structure resembling the Wi-Fi symbol and the electrodes are spaced 120° apart for three-axis force detection. The proposed sensor consists of three main components: a top plate, a sensing part, and a bottom part. The stiffness of the deformed part of the top plate is determined by analyzing the corresponding design parameters. The Wi-Fi-shaped electrode structures are located in the sensing part, and the capacitance information of the electrodes is measured. The proposed sensor has a high resolution (2.72 mN/digit), a wide measurement range (100 N), and compactness (thickness: 6.6 mm) and offers the advantages of a low cost and ease of manufacture. The sensor performance was verified through experiments conducted in an environment combined with an actual robot manipulator.
Keywords: Capacitive sensor; compact sensor; multiaxis force sensor; sensitivity amplification mechanism